School Libraries in Gulbarga City - Goutami; Tadasad, P. G. (Journal of Information and Knowledge, 2008)
The libraries in school level play an important role in developing and improving the child psychology, learning capacity and also help in supporting the curriculum needs of the teachers and pupils. But it is noted that majority of the schools in India as well as in Karnataka state have no library. Even though few schools are having libraries, there is inadequate infrastructure, such as, lack of independent building, less collection kept in closed access, management of library by non-library professionals, shortage of reading room and furniture, etc. The present study is made to assess the problems of the school libraries in Gulbarga city. The paper revealed that there are 184 school libraries and the present study covered about 144 school libraries. It is also noted that of these school libraries under the study, only 88 schools are having their own libraries. The paper included the different problems such as library professionals, independent library building, collection, etc. The paper concluded with the remarks that the authority of the schools and government has to establish the libraries in their schools and also solve problems of school libraries in different aspects.